2023
DOI: 10.1038/s41467-023-38086-4
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency and stable short-delayed fluorescence emitters with hybrid long- and short-range charge-transfer excitations

Abstract: The pursuit of ideal short-delayed thermally activated delayed fluorescence (TADF) emitters is hampered by the mutual exclusion of a small singlet-triplet energy gap (ΔEST) and a large oscillator strength (f). Here, by attaching an multiresonance-acceptor onto a sterically-uncrowded donor, we report TADF emitters bearing hybrid electronic excitations with a main donor-to-acceptor long-range (LR) and an auxiliary bridge-phenyl short-range (SR) charge-transfer characters, balancing a small ΔEST and a large f. Mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…18c) as a fluorescent emitter with hybrid long-and short-range CT excitations. 113 The well-balanced rate constants of k r c k ISC E k RISC 4 10 6 s À1 lead to a short t DF of E 0.88 ms. The quasiplanar structure of 2BOICz gives a favoured dipole orientation for a large outcoupling efficiency.…”
Section: Indolocarbazole Indenocarbazole Benzofurocarbazole Benzothie...mentioning
confidence: 97%
“…18c) as a fluorescent emitter with hybrid long-and short-range CT excitations. 113 The well-balanced rate constants of k r c k ISC E k RISC 4 10 6 s À1 lead to a short t DF of E 0.88 ms. The quasiplanar structure of 2BOICz gives a favoured dipole orientation for a large outcoupling efficiency.…”
Section: Indolocarbazole Indenocarbazole Benzofurocarbazole Benzothie...mentioning
confidence: 97%
“…77–79 Typically, a TADF chromophore consists of the individual electron acceptor (A) and electron donor (D) fragments. 80,81 A small energy gap Δ E (S1–T1) between T 1 and S 1 is required to achieve efficient RISC at room temperature (Δ E (S1–T1) < 0.2 eV). 82–84 A general strategy to obtain a small Δ E (S1–T1) in pure organic systems is through a twisting intramolecular charge transfer (TICT) strategy, requiring the design of organic TADF molecules with different D and A fragments, thereby reducing the overlap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO).…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the b series molecules tend to exhibit more efficient RISC compared to the a and c series molecules owing to their moderate Δ E ST and large SOC values, and the f and k r are gradually decreased for the a, b, and c series molecules with increasing CT proportion (declining hole–electron overlap). Therefore, a small Δ E ST and large SOC for a fast RISC process, a large f for an efficient radiative rate, and a narrow fwhm for high color purity could be simultaneously obtained in MR-TADF emitters by precisely regulating the hybrid long-range and short-range electronic excitations of emitters …”
mentioning
confidence: 99%
“…Multiple resonance (MR)-TADF emitters containing suitably positioned electron-donating atoms (e.g., N, O, and S) and electron-withdrawing atoms/groups (e.g., B and C=O) within the fused aromatic framework exhibit frontier molecular orbitals (FMOs) localized on the adjacent atoms/groups, leading to small Δ E ST and large SOC required for the RISC process. Such structural features also minimize bonding/antibonding characters and molecular relaxations, which is favorable for narrowband emissions . Although more than 200 MR-TADF materials have been reported since the first demonstration by Hatakeyama et al in 2016, the majority show blue or green emission. Developing longer-wavelength MR-TADF materials is still full of challenges due to the intrinsic difficulties associated with the energy gap law and the bathochromic shifts of the MR-induced emissions …”
mentioning
confidence: 99%
See 1 more Smart Citation